The Influence of Customer Engangement, Customer Loyalty and Customer Experience on Sales Achievement (Kasus: Imunicare by Bio Farma) - Edwin Rukmansyah (Publikasi Indonesia, 2024)
The Indonesian Ministry of SOEs has officially authorized the operation of the Pharmaceutical Holding in early 2020, one of which is Bio Farma. Bio Farma has carried out business development with the immunicare brand which is engaged in vaccination services with a partnership business model. In a business, customer satisfaction and loyalty are obtained through partnerships and digital marketing, thus reflecting the importance of effective leadership in designing and implementing initiatives that support company productivity and growth. The research method used is descriptive with a quantitative approach. The total population of immunicare partners was 216 with a sample taken to represent the population of 140 respondents after rounding. The data collection tools used are documentation studies and questionnaires. Furthermore, data analysis is carried out using the SmartPLS application. The results showed that the variables of satisfaction, trust, commitment, sensory, affection, behavior, intellectual, satisfaction with the brand, price perception, and return scheme have a positive and significant influence on customer engagement, experience, and loyalty to the Bio Farma company and Immunicare brand products, which have an impact on increasing sales and company revenue with indicators that can vary depending on the type of customer observed.